2019
DOI: 10.15644/asc53/3/6
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Determinants and Common Reasons for Visiting the Emergency Dental Service in the City of Zagreb

Abstract: ObjectiveThe objective of the study was to determine the sociodemographic and clinical parameters of patients who visit the emergency dental service and their most common diagnoses.Materials and MethodsThe data were collected on the basis of a survey filled out by patients. A total of 1730 out of 6732 patients (26%) were surveyed using a questionnaire to analyze sociodemographic status, dental visits, the description and dynamics of the symptoms. After the data collection, methods of descriptive data presentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…However, in the present study, only 31% of the patients had either no healthcare insurance or minimal coverage (AME, CMUs), indicating that not only is the DEU a recourse for socioeconomically disadvantaged individuals; the DEU of the GHPS might also be considered more as a first line setting than as a recourse setting since only 6.7% of patients were examined and referred by a dentist before coming to the DEU, although less than 15% of the emergencies were life-threatening conditions (cellulitis, hemorrhages) or traumas. This first-visit rate is high and comparable to [ 70 , 71 ] where 80% and 56% of patients were found to directly attend the DEU. As in France 86% of the dentists work in private offices, 12% are employed in private centers or company/association settings, and only 2% work in public hospitals [ 72 ], this suggests an inability of the actual health system to adequately respond to dental emergencies.…”
Section: Discussionsupporting
confidence: 68%
“…However, in the present study, only 31% of the patients had either no healthcare insurance or minimal coverage (AME, CMUs), indicating that not only is the DEU a recourse for socioeconomically disadvantaged individuals; the DEU of the GHPS might also be considered more as a first line setting than as a recourse setting since only 6.7% of patients were examined and referred by a dentist before coming to the DEU, although less than 15% of the emergencies were life-threatening conditions (cellulitis, hemorrhages) or traumas. This first-visit rate is high and comparable to [ 70 , 71 ] where 80% and 56% of patients were found to directly attend the DEU. As in France 86% of the dentists work in private offices, 12% are employed in private centers or company/association settings, and only 2% work in public hospitals [ 72 ], this suggests an inability of the actual health system to adequately respond to dental emergencies.…”
Section: Discussionsupporting
confidence: 68%
“… 12 In Croatia, the most common diagnosis was face and jaw abscesses (27.3%). 13 A previous study about dental emergencies conducted in a medical center's hospital found that 20.9% of dental emergencies were caused from trauma and 46.7% came from pulp or periodontal related problems in Taiwan. 14 Also, 47.1% of paediatric dental emergencies were caused from trauma in 2012–2013.…”
Section: Discussionmentioning
confidence: 99%